Drawing lines and circles in Parkinson's Disease: The lateralized symptoms interfere with the movements of the unaffected hand. (22nd January 2021) - Scarpina, Federica; Bruno, Valentina; Rabuffetti, Marco; Priano, Lorenzo; Tagini, Sofia; Gindri, Patrizia; Mauro, Alessandro; Garbarini, Francesca
Abstract: Introduction: Evidence about altered bimanual coordination has been reported in Parkinson's Disease. However, no previous study has explored such an alteration quantifying the interference effect that the trajectory of each hand might impose on the other one. Thus, in the present research, we applied the traditional Circles-Lines Coupling Task, which allowed assessing the motor coordination of the two hands, in the context of Parkinson's Disease. Methods: Thirty-six individuals affected by Parkinson's Disease were consecutively recruited and assigned to two groups according to their symptoms' lateralization. Moreover, eighteen age-matched healthy controls participated in the study. We capitalized on the Circles-Lines Coupling Task, in which the performance during incongruent movements (drawing lines with one hand and circles with the other hand) was compared with the performance during congruent movements (drawing lines with both hands). A bimanual coupling index was computed to compare the interference effect of each hand on the other one. Results: In healthy controls, the bimanual coupling index did not differ between the two hands. Crucially, in both groups of individuals affected by Parkinson's Disease, the less affected hand showed a significantly higher bimanual coupling index, due to the abnormal interference exerted by the most affected one, than vice versa . Conclusions: Our results highlighted an altered spatial bimanual coupling in Parkinson's disease, depending on the symptoms' lateralization. We offered different explanations of our results according to the theoretical frameworks about the mechanisms subserving bimanual coordination. Highlights: Bimanual coupling is the natural propensity to coordinate hands movements. In Parkinson's Disease, bimanual coordination is altered. We study the spatial interference between hands in Parkinson's Disease. A higher bimanual coupling for the less affected hand.